2021
DOI: 10.21608/jaauth.2021.63042.1135
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Organizational Resilience and Human Resources Practices in the Hotel Industry.

Abstract: This study aimed to explore the impact of organizational resilience (OR) on human resources management practices (HRMP) in the resort hotels context. Structured interviews were conducted with fourteen managers, and a pre-tested self-administrated questionnaire was used to collect the required data for this study. The questionnaire was distributed to a random sample of 300 employees working in 11 five-star hotels in the Red Sea region. The findings showed that organizational resilience has a significant relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In connection with the findings above, in the setting of accommodation establishment, Hussien et al (2021) demonstrated that hotel employees are more likely to feel secure in their positions and have access to possibilities for training and professional growth within a supportive organizational culture. They will probably give back by supporting organizational objectives like organizational resilience methods through constructive organizational behaviors.…”
Section: Organizational Resilience and Hrmp Of Accommodation Establis...mentioning
confidence: 62%
See 4 more Smart Citations
“…In connection with the findings above, in the setting of accommodation establishment, Hussien et al (2021) demonstrated that hotel employees are more likely to feel secure in their positions and have access to possibilities for training and professional growth within a supportive organizational culture. They will probably give back by supporting organizational objectives like organizational resilience methods through constructive organizational behaviors.…”
Section: Organizational Resilience and Hrmp Of Accommodation Establis...mentioning
confidence: 62%
“…The data instrument used in this study was a questionnaire that has been adapted and adopted from the research conducted by Hussien et al (2021). The survey questionnaire consisted of three main parts and was employed in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations